Hepatoprotective Activity of Aegle marmelos in CCl4 Induced Toxicity - An In-vivo Study - T. Thirunalasundari*, P. Sumitha and (Journal of Phytology, 2011)
Medicinal plants are of great importance for healthy living of an individual. Aegle marmelos is one of the Indian medicinal plant, which has enormous medicinal values against various diseases / disorders and it has traditionally been used by ayurvedic people for the treatment of liver problems. This study is aimed to investigate the hepatoprotective effect of crude ethanolic extract of the leaves of A. marmelos (AMEE) in carbon tetrachloride (CCl4) induced toxicity in mice. The ethanolic extract at a dose of 500mg/kg body weight when given orally exhibited a significant (P<0.05) protective effect evidenced by lowering the levels of enzymes like serum glutamate pyruvate transminase, serum glutamate oxaloacetate transminase, alkaline phosphatase, bilirubin, total cholesterol, triglycerides, low density lipoprotein and very low density lipoprotein but there was an increase in the level of high density lipoprotein as compared to CCl4 induced group. It was also proved by increased level of antioxidant enzymes in A. marmelos treated group. Lipid peroxidation was significantly lowered in CCl4 treated group followed by plant extract treated group. These biochemical observations were supported by histopathological examination of liver sections. From these results, it was concluded that the ethanolic extract of Aegle marmelos possesses hepatoprotective activity which needs to be proved further to get a lead molecule for hepatoprotection.